The Influence Of Storytelling Method Towards Moral Values Planting In PAUD Tunas Tadulako Palu - Nurhayati .; Andi Agusniatih; Amrullah .; Fitriana .; Sita Awalunisah (Universitas Muhammadiyah Ponorogo, 2020)
This study aims to find out how to cultivate moral values through the method of storytelling at PAUD Tunas Tadulako Palu. This research is an experiment, by providing treatment that begins with initial observation, treatment and final observation. The instruments used include: illustrated story books, dolls, imitation items, plants, pictures, and CD or videos. The results of the study indicate an increase in moral values that are quite good through the storytelling method. The method of planting moral values applied has a lot of positive influences on children's moral development and through appreciation of the content of the story, the child will gradually change his behavior which was not in accordance with existing moral values to be better in accordance with the character portrayed in the story.